The Intergenerational Transmission of Trauma, Adverse Childhood Experiences and Adverse Family Experiences: A Qualitative Exploration of Sibling Resilience - Miriam Riaz Nichol; Lee John Curley; Pamela Jane Sime (Behavioral Sciences)
The Adverse Childhood Experiences (ACEs) and Adverse Family Experiences (AFEs) frameworks have been employed extensively in research. However, to date, no such studies have considered both frameworks concurrently, nor have they explored the similarities and differences in resilience between siblings with ACE- and AFE-exposed parent(s). Doing so could, perhaps, establish the ways in which adversity is transmitted through generations and subsequently identify what trajectories to address in potential interventions. Thus, the objectives of this study were to examine the experiences of families with intergenerational ACE and AFE trauma, and to ascertain what influences similarities and differences in sibling resilience. The thematic analysis of two family case studies (n = 6) proposed a narrative encompassing fear, relationships and challenging trauma. Findings demonstrated the influence of neighbourhood violence which appeared to initiate this narrative. The fear associated with neighbourhood violence and maltreatment in early childhood appeared to influence both the parent–child bond and intimate relationships. Finally, participants demonstrated the protective properties of dissociation and sibling parentification, exhibiting their relationship with resilience. Investigators suggested neighbourhood violence be considered in the ACE questionnaire to inform current and future policies, and to safeguard the needs of families affected by intergenerational trauma.